Estimating International Tourism Demand for Laos PDR Using Panel ARDL Approach - Athikone Bouphanouvong (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This paper investigates the significance influence of economic factors in determining international tourism demands in Laos PDR using panel ARDL approach .Data collected was from 8 countries in ASEAN region based on sample of 9 years ( 2005 to 2013) and macroeconomic force acting for a given time affecting 9 year rates of return for listed in Thailand, Vietnam, Cambodia, Singapore, Philippine, Malaysia, Brunei and Indonesia. The impulses of 8 ASEAN macroeconomic forces Dt, GDPt, TPt, and POt acting for a given time influence the demand of tourists with both a domestic effect and an outsider effect at same period. The method was used based on Pooled Mean Group Estimator (PMGE), Mean Group Estimator (MGE) and Hausman Test to find long run and short run relationship of international tourism demand for Laos PDR. To test whether or not the data was stationary this research used five methods, including the LLC(2002) panel unit root test, IPS (2003) panel unit root test, PP (2001) panel unit root test,ADF panel unit root test this study found out the long run relationship between factors affecting by using PMG. The results are as follows. Variable lnGDP, lnPO and lnTP have long run relationship and also have positive effect on the international tourism demand for Laos PDR, in other word, when GDP of origin countries increases, price of fuel increases, and demand of tourist arrival to Laos increase too. The main variable rate is inversely proportional the GDP and shall be more effective on the supporting demand of foreign tourist arriving to Laos than Price of tourism and price of fuel. Also the result show that for short run relation between demand of tourism and determinant factors of lnGDP, lnPO and lnTP, those variable have short run relationship,in other word there is error term in the short run.so factors have significant to explain short run relationship.